Peter Shaffer's Amadeus - Forman, Milos; Shaffer, Peter 1926- (Warner Home Video, 1984)
The film presents the life and music of Wolfgang Amadeus Mozart. Viewed through the memories of an envious rival, Antonio Salieri, a mediocre 18th century Viennese composer obsessed with and jealous of the musical genius of the age.